Enhancing Sustainable Education through Strategic Information System Planning: A Case Study of Digital Learning Implementation at SMP Islam Darussalam - Adib Pakarbudi; Faraniena Yunaeni Risdiana; Faid Aulia Rachman; Tiara Indra Arifien; Hastiyan Ade Novianto (IAIN Madura, 2026)
This study aims to design a strategic information system plan to support digital learning implementation at SMP Islam Darussalam using the Ward and Peppard approach. The current implementation of e-learning at SMP Islam Darussalam is not yet optimal due to the absence of a well-defined strategic plan, resulting in misalignment between systems and user needs. Previous studies on IS/IT strategic planning have mainly focused on universities and business organizations, while limited research discusses its implementation in Islamic junior high schools. This study employs a qualitative case study approach. Data were collected through interviews, observations, and documentation. The analysis applies the Ward and Peppard framework, supported by SWOT, Value Chain, PEST, Porter’s Five Forces, and McFarlan Strategic Grid analyses. The results show that the approach effectively identifies organizational needs and formulates IS/IT strategies aligned with institutional goals. The study produces recommendations in the form of an application portfolio and development roadmap focusing on a Learning Management System (LMS), an online examination system, and a student performance analysis system to support sustainable digital learning implementation.